Migration of Croatian physicians in the global context : Migracija hrvatskih liječnika u globalnom kontekstu - Gruber, Ema (Array, 2020)
As the global health care workforce faces a shortage, several EU nations focus on employing foreign-trained physicians. So much so, that in some countries of the EU, the percentage of foreign-trained physicians has reached 30 % and the percentage of foreign-trained psychiatrists has risen to 40 %. After Croatia entered the EU, together with a significant number of other Croatian citizens, a great proportion of Croatian physicians emigrated. Currently, Croatia is among the three EU countries from which the most physicians emigrate. There are both economic and non-economic factors that are influence individuals’ choice to emigrate. Benefits of emigration for Croatian physicians are high satisfaction with life standard, income, professional development, and better work conditions. However, there are also clear psychological costs involved, which hinder both the emigrants and their families, and make building of a social network and integration into society difficult. These are: moving away from family members, friends and a familiar environment, mastering another language, finding work opportunities for partners, adjusting to life in another country under discrimination by colleagues, patients and the general public. Countries of immigration face challenges with foreign-trained physicians because of their native linguistic and cultural background. Language proficiency training and national familiarization programs can improve integration of immigrant physicians and their families. In recognition that national skill shortages can cause disbalance on a global level, the WHO calls on high-income countries to strive for self-sufficiency, through educating, retaining, and sustaining enough physicians to staff their own health care systems.